Gallstones ileus in young patient with incidental finding a small bowl carcinoid tumour - Ghaith, Ata M.; Alsekarnh, Mohammad I.; Awad, Ahmad K.; Ghaith, Osama M. (International Surgery Journal, 2023)
Gallstone ileus in young patient with incidental finding carcinoid of small bowel identified during exploration for proximal stones, both pathologies have no known pathological reasons to be associated with each other. We present a case of a 45-year-old male who presented with small bowel obstruction as an emergency. At laparotomy we found gall stone impacted in mid ileum and during exploration to exclude multiple proximal stones, small carcinoid identified in mid jejunum. Segmental small bowel resection was performed without disturbing the biliary pathology. Gallstone ileus may manifest in the younger population, and in the course of searching the small bowel to eliminate the presence of multiple stones proximal to the site of the impacted gallstone ileus other pathology may detected for which we incidentally identified asymptomatic carcinoid such case has never been reported before. Importance of a thorough laparotomy is emphasized.